High peel strength butyl hot melt sealant and method of making same
Patent Information
- Application Number
- CN202611083308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-20
AI Technical Summary
1.剥离强度不足:常规丁基热熔胶的90°剥离强度通常仅为0.6-2.4N/mm,难以达到4.0N/mm以上的高性能要求;
与现有技术相比,本发明具有以下有益效果:
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of sealant technology, specifically to a high peel strength butyl hot melt sealant and its preparation method. Background Technology
[0002] Butyl hot melt adhesive is a one-component adhesive made primarily of butyl rubber with added modifiers such as polyisobutylene. It features ultra-low water vapor permeability, high adhesion, and aging resistance, and is widely used for bonding and sealing in fields such as building waterproofing, automotive manufacturing, and new energy. Currently, the 90° peel strength of conventional butyl hot melt adhesives on the market is typically in the range of 0.6-2.4 N / mm, which is insufficient to meet the requirements of high-end applications requiring a peel strength of ≥4.0 N / mm.
[0003] The existing butyl hot melt adhesive technology mainly faces the following technical challenges: 1. Insufficient peel strength: The 90° peel strength of conventional butyl hot melt adhesives is usually only 0.6-2.4 N / mm, which is difficult to meet the high-performance requirement of 4.0 N / mm or more; 2. The contradiction between permanent non-curing and high peel strength: Existing technologies struggle to simultaneously achieve both permanent non-curing properties and ultra-high peel strength. Permanent non-curing requires materials to maintain a certain level of fluidity and self-healing ability, while high peel strength necessitates a stable cross-linked structure. These two aspects are difficult to achieve simultaneously using traditional technological approaches.
[0004] Chinese patent application CN111218240A discloses a dynamically cross-linked hot-melt butyl self-adhesive sealant, employing a one-step dynamic cross-linking process using brominated butyl rubber, phenolic resin cross-linking agent, and low-density polyethylene. However, its 90° peel strength is only 1.7 N / mm, failing to meet the peel strength requirements for high-end applications. Furthermore, its one-step dynamic cross-linking process cannot form a stable sea-island phase structure, limiting further improvements in peel strength. In conclusion, developing a high-peel-strength butyl hot-melt sealant with a 90° peel strength exceeding 4.0 N / mm and permanent non-curing properties is of significant technical importance and application value. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to provide a high peel strength butyl hot melt sealant and its preparation method to address the shortcomings of the prior art, thereby solving at least one of the above-mentioned technical problems.
[0006] The technical solution of this invention to solve the above-mentioned technical problems is as follows: A high peel strength butyl hot melt sealant and its preparation method, wherein the butyl hot melt sealant is composed of the following raw materials in parts by weight: 5-10 parts butyl rubber, 2-4 parts thermoplastic elastomer, 18-25 parts polyisobutylene, 3-5 parts plasticizer, 18-25 parts tackifier, 35-45 parts filler, 2-3.5 parts additives, 0.5-2 parts thixotropic agent, 0.3-1 part vulcanizing agent, 0.1-0.5 parts coupling agent, and 0.1-0.5 parts antioxidant.
[0007] Preferably, the butyl hot melt sealant has a sea-island phase structure, wherein the vulcanized butyl rubber is dispersed in the continuous phase of thermoplastic elastomer in the form of microparticles with a particle size of 1-5 μm.
[0008] Preferably, the gel content of the vulcanized butyl rubber is 60%-70%.
[0009] Preferably, the thermoplastic elastomer is one or a combination of several of the following: polypropylene, styrene-ethylene-butene-styrene block copolymer, ethylene-octene copolymer, styrene-isoprene-styrene block copolymer, or ethylene-vinyl acetate copolymer.
[0010] Preferably, the filler is one or a combination of several of the following: light calcium carbonate, heavy calcium carbonate, talc, kaolin, wollastonite, nano calcium carbonate, or carbon black.
[0011] Preferably, the vulcanizing agent is a phenolic resin vulcanization system, which includes phenolic resin and a vulcanization accelerator.
[0012] Preferably, the sulfidation accelerator is one or a combination of several of stannous chloride, zinc chloride, zinc oxide, or stearic acid.
[0013] A method for preparing a high peel strength butyl hot melt sealant, characterized by comprising the following steps: Step S1: Raw material inspection. All raw materials used in production are inspected upon arrival at the factory to ensure that they are all qualified products. Step S2: Ingredient preparation. Weigh and prepare each ingredient according to the formula sheet. Step S3: Premixing. Butyl rubber, thermoplastic elastomer and some filler are added to a kneader and mixed for 30-40 minutes at a temperature of 140-160℃ and a speed of 40±5Hz. The order of adding materials is butyl rubber → thermoplastic elastomer → filler to obtain masterbatch. The aforementioned portion of the filler accounts for 60%-80% of the total filler volume, and the remaining filler is added in step S5; Step S4: Dynamic vulcanization. Add vulcanizing agent to the masterbatch and dynamically vulcanize for 10-20 minutes at a temperature of 145-165℃ and a rotation speed of 40±5Hz to obtain a thermoplastic vulcanized rubber intermediate. In the thermoplastic vulcanized rubber intermediate, vulcanized butyl rubber is uniformly dispersed in the continuous phase of thermoplastic elastomer in the form of microparticles with a particle size of 1-5 μm, forming a sea-island phase structure. Step S5: Secondary mixing. Cool the thermoplastic vulcanized rubber intermediate to 130-140℃, and add the tackifier, polyisobutylene, plasticizer, remaining filler, thixotropic agent, coupling agent, additives and antioxidant in sequence. The total mixing time is 40-50 minutes to obtain butyl hot melt sealant. Step S6: Discharge and cooling. The butyl hot melt sealant obtained in step S5 is extruded through a screw extruder at 105-115℃ and cooled naturally to obtain the high peel strength butyl hot melt sealant product.
[0014] Preferably, the dynamic vulcanization ends when at least two of the following three endpoint criteria are met: ① the kneader current curve tends to be stable with fluctuation amplitude < 5% of the rated current; ② the rebound rate after pressing for 10 seconds by an online sample rebound hammer test is > 80%; ③ the gel content determined by the equilibrium swelling method is 60%-70%.
[0015] Preferably, dynamic vulcanization is defined as the vulcanization endpoint being the fulfillment of all three endpoint criteria. The beneficial effects of this invention are: Compared with the prior art, the present invention has the following beneficial effects: 1. Ultra-high peel strength: The butyl hot melt sealant of this invention has a 90° peel strength ≥4.0N / mm, which is 1.7-6.7 times that of conventional products (0.6-2.4N / mm), meeting the high-end application needs of building waterproofing, automobile manufacturing, new energy and other fields.
[0016] 2. Permanent non-curing properties: This invention utilizes an ocean-island phase structure (cured butyl rubber microparticles are uniformly dispersed in a continuous thermoplastic elastomer phase) to enable the material to maintain a certain degree of fluidity and self-healing ability during long-term use.
[0017] 3. Stable sea-island phase structure: Through a two-stage process—first, dynamic vulcanization to form the sea-island structure in the TPV intermediate, and then cooling and mixing to protect the integrity of the phase—vulcanized butyl rubber is stably dispersed in the form of 1-5μm particles. Attached Figure Description
[0018] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the embodiments will be briefly introduced below. It should be understood that the following drawings only show some embodiments of the present invention and should not be regarded as a limitation of the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative effort.
[0019] Figure 1This is a flowchart illustrating the preparation process of the high peel strength butyl hot melt sealant of the present invention.
[0020] Figure 2 This is a schematic diagram of the marine-island phase structure of the high peel strength butyl hot melt sealant of the present invention. The dark spherical particles in the figure are vulcanized butyl rubber microparticles (island phase, particle size 1-5μm), and the light background is the thermoplastic elastomer continuous phase (marine phase). Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are some embodiments of the present invention, but not all embodiments. Generally, the components of the embodiments of the present invention described and shown in the accompanying drawings can be arranged and designed in various different configurations.
[0022] Therefore, the following detailed description of the embodiments of the invention provided in the accompanying drawings is not intended to limit the scope of the claimed invention, but merely to illustrate selected embodiments of the invention. All other embodiments obtained by those skilled in the art based on the embodiments of the invention without inventive effort are within the scope of protection of the invention.
[0023] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.
[0024] In the description of this invention, it should be noted that the terms "center," "upper," "lower," "left," "right," "vertical," "horizontal," "inner," and "outer," etc., indicate the orientation or positional relationship based on the orientation or positional relationship shown in the accompanying drawings, or the orientation or positional relationship commonly used when the product of this invention is in use. They are only for the convenience of describing this invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this invention. In addition, the terms "first," "second," "third," etc., are only used to distinguish descriptions and should not be construed as indicating or implying relative importance.
[0025] Furthermore, terms such as "horizontal" and "vertical" do not imply that components must be absolutely horizontal or suspended, but rather that they can be slightly tilted. For example, "horizontal" simply means that its direction is more horizontal than "vertical," and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0026] In the description of this invention, it should also be noted that, unless otherwise explicitly specified and limited, the terms "set," "install," "connect," and "link" should be interpreted broadly. For example, they can refer to a fixed connection, a detachable connection, or an integral connection; they can refer to a mechanical connection or an electrical connection; they can refer to a direct connection or an indirect connection through an intermediate medium; and they can refer to the internal connection of two components. Those skilled in the art can understand the specific meaning of the above terms in this invention based on the specific circumstances.
[0027] Example 1: See Figures 1 to 2 The diagram below illustrates the present invention. The high peel strength butyl hot melt sealant of this embodiment is prepared according to the formula shown in Table 1 (based on a total formula of 100 parts by weight):
[0028] Table 1 Formulation of Example 1 The preparation method includes the following steps: (1) Raw material inspection: All raw materials are inspected upon arrival at the factory to ensure that they are all qualified products.
[0029] (2) Ingredients: Weigh each ingredient according to the recipe in Table 1.
[0030] (3) Premixing: 7.16 parts of butyl rubber, 2.60 parts of thermoplastic elastomer SEBS and filler light calcium carbonate (accounting for 70% of the total filler, i.e. 27.34 parts) are added to the kneader in sequence and mixed at 150℃ and 40Hz for 35 minutes. The order of adding materials is butyl rubber → thermoplastic elastomer → filler to obtain masterbatch.
[0031] (4) Dynamic vulcanization: Add 0.65 parts of vulcanizing agent phenolic resin and vulcanization accelerator stannous chloride to the masterbatch and vulcanize dynamically for 15 min at 155℃ and 40Hz. Dynamic vulcanization is considered to have reached the endpoint when all three endpoint criteria are met: ① the kneader current curve tends to be stable with fluctuation amplitude < 5% of the rated current; ② the rebound rate after pressing for 10s by online sampling and rebound hammer test is > 80%; ③ the gel content determined by the equilibrium swelling method reaches 63.1%. TPV intermediate is obtained, in which vulcanized butyl rubber is uniformly dispersed in the SEBS continuous phase in the form of particles with a particle size of 1-5μm, forming a sea-island phase structure.
[0032] (5) Secondary mixing: The TPV intermediate was cooled to 135°C, and 22.14 parts of C5 hydrogenated petroleum resin, 20.18 parts of polyisobutylene, 3.91 parts of naphthenic oil, 11.72 parts of light calcium carbonate (remaining filler), 1.30 parts of fumed silica (thixotropic agent), 0.20 parts of KH-5600 coupling agent, 2.60 parts of additives, and 0.20 parts of antioxidant 10100 were added in sequence. The total mixing time was 45 min to obtain butyl hot melt sealant.
[0033] (6) Discharge and Cooling: The butyl hot melt sealant was extruded at 110℃ using a screw extruder and then naturally cooled to below 40℃ at room temperature to obtain the high peel strength butyl hot melt sealant product. The performance of the prepared butyl hot melt sealant was tested, and the results are as follows: the 90° peel strength was 4.5 N / mm (tested according to GB / T2792-2014, the substrate was stainless steel plate, the sample width was 24 mm, and the peel speed was 300 mm / min), the penetration was 70 (0.1 mm / 5 s), there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test, and no cracking, hardening, or loss of tack after the 120℃ / 168h heat aging test. The failure mode in the 90° peel strength test was cohesive failure.
[0034] The above-mentioned "based on a total formula of 100 parts by weight" is only a formula calculation method for the embodiment and does not constitute any limitation on the range of parts by weight claimed in the claims.
[0035] Example 2: The difference between this example and Example 1 is as follows: Polypropylene (PP) was used as the thermoplastic elastomer, with a dosage of 3.0 parts; polyisobutylene with a molecular weight of 1000 was used, with a dosage of 22.0 parts; C5 / C9 copolymer petroleum resin was used as the tackifier, with a dosage of 20.0 parts; white oil was used as the plasticizer, with a dosage of 4.0 parts; KH-570 was used as the coupling agent, with a dosage of 0.3 parts; and organobentonite was used as the thixotropic agent, with a dosage of 1.5 parts. The premixing temperature was 145℃, the rotation speed was 40Hz, and the time was 30 min; the dynamic vulcanization temperature was 150℃, and the time was 18 min; the secondary mixing temperature was 132℃, and the total time was 42 min; the discharge temperature was 108℃. The performance of the prepared butyl hot melt sealant was tested, and the results are as follows: the 90° peel strength is 4.2 N / mm, the penetration is 68 (0.1 mm / 5 s), and the heat resistance and heat aging test results are consistent with those of Example 1.
[0036] Example 3: The difference between this example and Example 1 is as follows: the thermoplastic elastomer used is ethylene-octene copolymer (POE), with a dosage of 2.5 parts; the polyisobutylene used is a grade with a molecular weight of 3000, with a dosage of 19.0 parts; the tackifier used is rosin glycerol ester, with a dosage of 24.0 parts; the plasticizer used is naphthenic oil, with a dosage of 4.5 parts; the coupling agent used is KH-550, with a dosage of 0.4 parts; the thixotropic agent used is polyamide wax, with a dosage of 1.0 part; and the antioxidant used is antioxidant 1076, with a dosage of 0.15 parts. The premixing temperature is 158℃, the rotation speed is 42Hz, and the time is 38min; the dynamic vulcanization temperature is 160℃, and the time is 12min; the secondary mixing temperature is 138℃, and the total time is 48min; the discharge temperature is 113℃. The performance of the prepared butyl hot melt sealant was tested, and the results are as follows: the 90° peel strength is 4.1 N / mm, the penetration is 72 (0.1 mm / 5 s), and the heat resistance and heat aging test results are consistent with those of Example 1.
[0037] Example 4: This example verifies the upper limit of the dosage of multiple components in claim 1. The difference from Example 1 is as follows: butyl rubber is 10.0 parts (upper limit), thermoplastic elastomer SEBS is 3.5 parts, polyisobutylene is 18.0 parts (lower limit), plasticizer is 3.5 parts, tackifier C5 hydrogenated petroleum resin is 21.0 parts, filler light calcium carbonate is 36.5 parts, additives are 3.0 parts, thixotropic agent fumed silica is 1.0 part, vulcanizing agent is 0.8 parts, coupling agent KH-560 is 0.3 parts, and antioxidant 1010 is 0.3 parts. The premixing temperature is 152℃, the rotation speed is 40Hz, and the time is 33 min; the dynamic vulcanization temperature is 158℃, and the time is 16 min; the secondary mixing temperature is 135℃, and the total time is 46 min; the discharge temperature is 112℃. The gel content is 64.5%. The prepared butyl hot melt sealant was subjected to performance tests: the 90° peel strength was 4.6 N / mm, the penetration was 68 (0.1 mm / 5 s), and there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test. After the 120℃ / 168h heat aging test, there was no cracking, hardening, or loss of tack.
[0038] Example 5: This example verifies the lower limits of the dosage of multiple components in claim 1. The difference from Example 1 is as follows: butyl rubber is 5.0 parts (lower limit), thermoplastic elastomer SEBS is 2.0 parts (lower limit), polyisobutylene is 25.0 parts (upper limit), plasticizer naphthenic oil is 5.0 parts (upper limit), tackifier C5 hydrogenated petroleum resin is 22.0 parts, filler light calcium carbonate is 35.0 parts (lower limit), additives are 2.0 parts (lower limit), thixotropic agent fumed silica is 0.5 parts (lower limit), vulcanizing agent is 0.5 parts, coupling agent KH-560 is 0.5 parts (upper limit), and antioxidant 1010 is 0.2 parts. The premixing temperature is 142℃, the rotation speed is 38Hz, and the time is 38min; the dynamic vulcanization temperature is 148℃, and the time is 18min; the secondary mixing temperature is 133℃, and the total time is 43min; the discharge temperature is 108℃. The gel content was 60.8%. The performance of the prepared butyl hot melt sealant was tested: the 90° peel strength was 4.0 N / mm, the penetration was 73 (0.1 mm / 5 s), and there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test. After the 120℃ / 168h heat aging test, there was no cracking, hardening, or loss of tack.
[0039] Example 6: This example verifies the feasibility of using thermoplastic elastomer PP under the upper limit of dosage and the endpoints of filler / tackifier dosage. The difference from Example 1 is: butyl rubber dosage is 8.0 parts, thermoplastic elastomer PP dosage is 4.0 parts (upper limit), polyisobutylene dosage is 18.0 parts (lower limit), plasticizer white oil dosage is 3.0 parts (lower limit), tackifier C5 / C9 copolymer petroleum resin dosage is 18.0 parts (lower limit), filler light calcium carbonate dosage is 45.0 parts (upper limit), additives dosage is 2.5 parts, thixotropic agent organic bentonite dosage is 0.8 parts, vulcanizing agent dosage is 1.0 part (upper limit), coupling agent KH-570 dosage is 0.5 parts (upper limit), and antioxidant 1010 dosage is 0.2 parts. The premixing temperature was 155℃, the rotation speed was 40Hz, and the time was 32min; the dynamic vulcanization temperature was 162℃ and the time was 14min; the secondary mixing temperature was 136℃ and the total time was 44min; the discharge temperature was 110℃. The gel content was 67.8%. The performance of the prepared butyl hot melt sealant was tested: the 90° peel strength was 4.4N / mm, the penetration was 66 (0.1mm / 5s), and there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test. After the 120℃ / 168h heat aging test, there was no cracking, hardening, or loss of tack.
[0040] Example 7: This example verifies the feasibility of using the lower limit (0.3 parts) of the vulcanizing agent and the upper limit (0.4 parts) of the antioxidant. The difference from Example 1 is that the amount of butyl rubber is 7.0 parts, the amount of thermoplastic elastomer SEBS is 3.0 parts, the amount of polyisobutylene is 20.0 parts, the amount of plasticizer naphthenic oil is 4.0 parts, the amount of tackifier rosin glycerol ester is 25.0 parts (upper limit), the amount of filler light calcium carbonate is 36.0 parts, the amount of additives is 2.8 parts, the amount of thixotropic agent fumed silica is 1.0 part, the amount of vulcanizing agent is 0.3 parts (lower limit), the amount of coupling agent KH-550 is 0.5 parts (upper limit), and the amount of antioxidant 1076 is 0.4 parts. The premixing temperature was 148℃, the rotation speed was 40Hz, and the time was 35min; the dynamic vulcanization temperature was 153℃ and the time was 20min (the vulcanization time was appropriately extended to ensure the gel content met the standard due to the lower limit of the vulcanizing agent dosage); the secondary mixing temperature was 134℃ and the total time was 47min; the discharge temperature was 109℃. The gel content was 60.5%. The performance of the prepared butyl hot melt sealant was tested: the 90° peel strength was 4.0N / mm, the penetration was 73 (0.1mm / 5s), and there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test. After the 120℃ / 168h heat aging test, there was no cracking, hardening, or loss of tack.
[0041] Example 8: This example verifies the feasibility of the upper limit (2.0 parts) of the thixotropic agent dosage, the lower limit (0.1 parts) of the coupling agent dosage, and the upper limit (3.5 parts) of the additive dosage. The difference from Example 1 is that: the dosage of butyl rubber is 7.5 parts, the dosage of thermoplastic elastomer EVA is 3.0 parts, the dosage of polyisobutylene is 19.0 parts, the dosage of plasticizer DOP is 5.0 parts (upper limit), the dosage of tackifier terpene resin is 20.0 parts, the dosage of filler talc is 38.0 parts, the dosage of additives is 3.5 parts, the dosage of thixotropic agent polyamide wax is 2.0 parts (upper limit), the dosage of vulcanizing agent is 0.5 parts, the dosage of coupling agent titanate NDZ-201 is 0.1 parts (lower limit), and the dosage of antioxidant 1010 is 0.3 parts. The premixing temperature was 145℃, the rotation speed was 40Hz, and the time was 36min; the dynamic vulcanization temperature was 155℃ and the time was 15min; the secondary mixing temperature was 132℃ and the total time was 45min; the discharge temperature was 106℃. The gel content was 63.0%. The performance of the prepared butyl hot melt sealant was tested: the 90° peel strength was 4.3N / mm, the penetration was 69 (0.1mm / 5s), and there was no slippage, flow, or deformation in the 100℃ / 2h heat resistance test. After the 120℃ / 168h heat aging test, there was no cracking, hardening, or loss of tack.
[0042] Comparative Example 1 (using a one-step dynamic crosslinking process): This comparative example uses a one-step dynamic crosslinking process. Instead of pre-preparing TPV intermediates, brominated butyl rubber, phenolic resin, and low-density polyethylene are directly mixed and crosslinked at 150-170℃, then compounded with other components to form a sealant. Performance tests were performed on the prepared sealant: the 90° peel strength was 1.7 N / mm; the microstructure showed uneven rubber phase distribution, with some continuous rubber networks and no clear sea-island phase structure. These results indicate that the one-step dynamic crosslinking method cannot form a stable sea-island phase structure, and the peel strength is far lower than that of this invention (1.7 vs ≥ 4.0 N / mm).
[0043] Comparative Example 2 (No dynamic vulcanization, purely physical blending): This comparative example did not add a vulcanizing agent. Butyl rubber, thermoplastic elastomer, polyisobutylene, filler, tackifier, and plasticizer were simply physically blended at 150°C and directly discharged. Performance tests were performed on the prepared sealant: the 90° peel strength was 0.9 N / mm, the penetration was >100 (0.1 mm / 5 s), the cohesive strength was severely insufficient, and significant flow was observed during the 100°C / 2h heat resistance test. These results verify the necessity of the dynamic vulcanization step for achieving high peel strength and heat resistance.
[0044] Performance testing methods: 90° peel strength: Tested according to GB / T2792-2014 "Test Method for Peel Strength of Adhesive Tapes", with stainless steel plate as the substrate, sample width 24mm, peel speed 300mm / min, and ambient temperature (23±2)℃ and relative humidity (50±5)%. Penetration: Tested according to GB / T4509-2010 "Determination of Penetration of Asphalt", with test conditions of 5s and 25℃. Heat resistance: Placed in a 100℃ constant temperature oven for 2 hours, observe for slippage, flow, or deformation. Thermal aging: Placed in a 120℃ constant temperature oven for 168 hours, observe for cracking, hardening, or loss of adhesion. Gel content: Using the equilibrium swelling method, the sample was placed in cyclohexane for 48 hours to swell, and the insoluble matter was weighed. Gel content = (mass of insoluble matter after swelling / total mass of butyl rubber phase) × 100%. Microstructure: The marine-island phase structure and particle size distribution of vulcanized rubber particles were observed using scanning electron microscopy (SEM) or transmission electron microscopy (TEM).
[0045] Industrial Applications: The high peel strength butyl hot melt sealant of this invention can be widely used in building waterproof membranes, automotive manufacturing seals, new energy battery seals, electronic component potting and other fields.
[0046] Appendix: Summary of Component Dosage in Examples The table below summarizes the component amounts (parts by weight) of each embodiment and comparative example to demonstrate full coverage of the scope of the claims of this invention:
[0047] Table 2 Summary of component dosages for each embodiment (parts by weight) As shown in Table 2, the eight embodiments cover the upper and lower limits of the dosage of all 11 components in claim 1. The 90° peel strength of all embodiments reaches above 4.0 N / mm, the penetration is between 66-73 (0.1 mm / 5 s), and the heat resistance test at 100℃ / 2h and the heat aging test at 120℃ / 168h are all qualified, which proves the sufficiency and feasibility of the scope of protection of the claims.
[0048] In this invention, "gel content of vulcanized butyl rubber" refers to the percentage by mass of the solid residue remaining after the cross-linked three-dimensional network of vulcanized butyl rubber formed by dynamic vulcanization of the thermoplastic vulcanized rubber intermediate prepared in this invention, which is insoluble in the solvent, after swelling in cyclohexane for 48 hours. A gel content of 60%-70% indicates that the butyl rubber is in a partially vulcanized state—the cross-linked portion (60%-70%) provides cohesive strength and peel strength, while the uncross-linked portion (30%-40%) retains the fluidity and self-healing ability of the molecular chain segments, which is the chemical structural basis for achieving the unity of "permanent non-curing" characteristics and high peel strength.
[0049] The preferred solutions for each component are further explained below: Butyl rubber: In this invention, butyl rubber serves as the basic skeleton material, providing the foundation for the sealant's elasticity, airtightness, and weather resistance. When the amount of butyl rubber is less than 5 parts, the cohesive strength of the sealant is insufficient, and the peel strength is difficult to reach 4.0 N / mm; when the amount is greater than 10 parts, the viscosity of the rubber compound is too high, which is not conducive to the uniform formation of the marine-island phase structure during dynamic vulcanization. Examples 5 (5 parts of butyl rubber) and 4 (10 parts of butyl rubber) respectively verified the feasibility of the upper and lower limits of this component, and the prepared sealants achieved 90° peel strengths of 4.0 N / mm and 4.6 N / mm, respectively.
[0050] Thermoplastic elastomer: preferably one or a combination of polypropylene (PP), styrene-ethylene-butene-styrene block copolymer (SEBS), ethylene-octene copolymer (POE), styrene-isoprene-styrene block copolymer (SIS), or ethylene-vinyl acetate copolymer (EVA). The thermoplastic elastomer acts as the continuous phase of the TPV during dynamic vulcanization, forming a stable sea-island structure with the vulcanized butyl rubber microparticles. Examples 1 (SEBS), 2 (PP), 3 (POE), and 8 (EVA) respectively verified that different types of thermoplastic elastomers can form the target sea-island phase structure, with peel strength ≥4.0 N / mm. Examples 5 (2 parts) and 6 (4 parts) verified the upper and lower limits of the dosage.
[0051] Polyisobutylene: a key modifying component of this invention, providing initial and permanent tack, and improving the elongation and weather resistance of the colloid. Low molecular weight polyisobutylene with a number average molecular weight of 1000-3000 is preferred. Example 2 used polyisobutylene with a molecular weight of 1000, and Example 3 used polyisobutylene with a molecular weight of 3000; both achieved a peel strength of ≥4.0 N / mm, indicating that polyisobutylene within this molecular weight range is suitable for this invention. Examples 4 and 6 (18 samples) verified the lower limit, and Example 5 (25 samples) verified the upper limit.
[0052] Tackifier: Preferably, it is one or a combination of several of C5 petroleum resin, C9 petroleum resin, C5 / C9 copolymer petroleum resin, hydrogenated petroleum resin, terpene resin, rosin resin, or rosin glycerol ester, providing initial tack and holding power. Example 1 used C5 hydrogenated petroleum resin, Example 2 used C5 / C9 copolymer petroleum resin, Examples 3 and 7 used rosin glycerol ester, and Example 8 used terpene resin; all achieved the target performance. Examples 6 (18 parts) and 7 (25 parts) verified the upper and lower limits of the dosage.
[0053] Plasticizer: Preferably, it is one or a combination of naphthenic oil, white oil, paraffin oil, dioctyl phthalate (DOP), or dibutyl phthalate (DBP) to provide plasticizing effect and elongation. Examples 1-5 and 7 used naphthenic oil, Examples 2 and 6 used white oil, and Example 8 used DOP. Examples 6 (3 parts) and Examples 5 and 8 (5 parts) verified the upper and lower limits of the dosage.
[0054] Filler: Preferably, it is one or a combination of several of the following: light calcium carbonate, heavy calcium carbonate, talc, kaolin, wollastonite, nano calcium carbonate, or carbon black, more preferably light calcium carbonate with a mesh size ≥ 800 mesh. The filler mainly serves to reinforce and reduce costs. Examples 1-7 used light calcium carbonate, and Example 8 used talc. Examples 5 (35 parts) and 6 (45 parts) verified the upper and lower limits of the dosage.
[0055] Additives: These are one or more of processing aids, antioxidant synergists, or dispersants used to improve the processing performance of the adhesive compound. In this invention, the amount of additive used is 2-4 parts. Example 5 verified the lower limit of 2 parts, Examples 1-3 used 2.6 parts, and Example 8 used the upper limit of 3.5 parts. Experimental data show that when the amount of additive exceeds 3.5 parts, the cohesive strength of the sealant begins to decrease, and the risk of additive exudation increases; when the amount is less than 2 parts, the improvement in processing performance is not significant. Therefore, 2-3.5 parts is the optimal range to balance processing performance and mechanical properties. It should be noted that the additive is added in step S5—if added in the dynamic vulcanization stage (145-165℃) of step S4, the low molecular weight organic components in the processing aid may volatilize or degrade under prolonged high-temperature shear, affecting its effectiveness.
[0056] Thixotropic agent: preferably one or a combination of several of fumed silica, organobentonite, polyamide wax, or hydrogenated castor oil, providing anti-sagging properties. Examples 1, 4, 5, and 7 used fumed silica; Examples 2 and 6 used organobentonite; and Examples 3 and 8 used polyamide wax. Examples 5 (0.5 parts) and 8 (2 parts) verified the upper and lower limits of the dosage.
[0057] Vulcanizing agent: This is a phenolic resin vulcanization system, comprising phenolic resin and a vulcanization accelerator. The vulcanization accelerator is preferably one or a combination of several of stannous chloride, zinc chloride, zinc oxide, or stearic acid. The vulcanizing agent is added during the dynamic vulcanization stage in step S4, causing partial cross-linking of the butyl rubber to form island-phase particles in the sea-island structure. Examples 7 (0.3 parts) and 6 (1 part) verified the upper and lower limits of the dosage. In Example 7, due to the relatively small amount of vulcanizing agent (0.3 parts), the vulcanization time was appropriately extended to 20 minutes to ensure that the gel content met the standard (60.5%).
[0058] Coupling agent: preferably one or a combination of several of silane coupling agents, titanate coupling agents, or aluminate coupling agents, used to improve the interfacial bonding between inorganic fillers and organic matrices. Example 1 used KH-560, Examples 2 and 6 used KH-570, Examples 3 and 7 used KH-550, and Example 8 used titanate NDZ-201. Examples 8 (0.1 parts) and Examples 5-7 (0.5 parts) verified the upper and lower limits of the dosage.
[0059] Antioxidant: Preferably, it is one or a combination of hindered phenolic antioxidants 1010, 1076, or phosphite antioxidants. Examples 1, 2, 4-6, and 8 used antioxidant 1010 (0.15-0.3 parts), Example 3 used antioxidant 1076 (0.15 parts), and Example 7 used antioxidant 1076 (0.4 parts). Experiments show that antioxidants in the range of 0.1-0.5 parts can effectively inhibit thermo-oxidative aging—when the dosage is less than 0.1 parts, the sealant shows a hardening trend after heat aging at 120℃ / 168h; when the dosage is more than 0.5 parts, the antioxidant effect tends to saturate and the cost increases. A comparison between Example 7 (0.4 parts) and Example 3 (0.15 parts) shows that both have qualified thermo-aging performance, indicating that this range has sufficient technical feasibility.
[0060] The above are merely optional embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various modifications and variations. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
[0061] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not describe the various possible combinations separately.
Claims
1. A high peel strength butyl hot melt sealant, characterized in that, The butyl hot melt sealant is composed of the following raw materials in parts by weight: 5-10 parts butyl rubber, 2-4 parts thermoplastic elastomer, 18-25 parts polyisobutylene, 3-5 parts plasticizer, 18-25 parts tackifier, 35-45 parts filler, 2-3.5 parts additives, 0.5-2 parts thixotropic agent, 0.3-1 part vulcanizing agent, 0.1-0.5 parts coupling agent, and 0.1-0.5 parts antioxidant.
2. The high peel strength butyl hot melt sealant according to claim 1, characterized in that: The butyl hot melt sealant has a sea-island phase structure, wherein the vulcanized butyl rubber is dispersed in the continuous thermoplastic elastomer phase as a particle with a particle size of 1-5 μm.
3. The high peel strength butyl hot melt sealant according to claim 1, characterized in that: The gel content of the vulcanized butyl rubber is 60%-70%.
4. The high peel strength butyl hot melt sealant according to claim 1, characterized in that: The thermoplastic elastomer is one or a combination of several of the following: polypropylene, styrene-ethylene-butene-styrene block copolymer, ethylene-octene copolymer, styrene-isoprene-styrene block copolymer, or ethylene-vinyl acetate copolymer.
5. The high peel strength butyl hot melt sealant according to claim 1, characterized in that: The filler is one or a combination of several of the following: light calcium carbonate, heavy calcium carbonate, talc, kaolin, wollastonite, nano calcium carbonate, or carbon black.
6. The high peel strength butyl hot melt sealant according to claim 1, characterized in that: The vulcanizing agent is a phenolic resin vulcanization system, which includes phenolic resin and a vulcanization accelerator.
7. The high peel strength butyl hot melt sealant according to claim 6, characterized in that: The sulfidation accelerator is one or a combination of several of stannous chloride, zinc chloride, zinc oxide, or stearic acid.
8. A method for preparing a high peel strength butyl hot melt sealant as described in any one of claims 1-7, characterized in that, Includes the following steps: Step S1: Raw material inspection. All raw materials used in production are inspected upon arrival at the factory to ensure that they are all qualified products. Step S2: Ingredient preparation. Weigh and prepare each ingredient according to the formula sheet. Step S3: Premixing. Butyl rubber, thermoplastic elastomer and some filler are added to a kneader and mixed for 30-40 minutes at a temperature of 140-160℃ and a speed of 40±5Hz. The order of adding materials is butyl rubber → thermoplastic elastomer → filler to obtain masterbatch. The aforementioned portion of the filler accounts for 60%-80% of the total filler volume, and the remaining filler is added in step S5; Step S4: Dynamic vulcanization. Add vulcanizing agent to the masterbatch and dynamically vulcanize for 10-20 minutes at a temperature of 145-165℃ and a rotation speed of 40±5Hz to obtain a thermoplastic vulcanized rubber intermediate. In the thermoplastic vulcanized rubber intermediate, vulcanized butyl rubber is uniformly dispersed in the continuous phase of thermoplastic elastomer in the form of microparticles with a particle size of 1-5 μm, forming a sea-island phase structure. Step S5: Secondary mixing. Cool the thermoplastic vulcanized rubber intermediate to 130-140℃, and add the tackifier, polyisobutylene, plasticizer, remaining filler, thixotropic agent, coupling agent, additives and antioxidant in sequence. The total mixing time is 40-50 minutes to obtain butyl hot melt sealant. Step S6: Discharge and cooling. The butyl hot melt sealant obtained in step S5 is extruded through a screw extruder at 105-115℃ and cooled to obtain the high peel strength butyl hot melt sealant product.
9. The method for preparing the high peel strength butyl hot melt sealant according to claim 8, characterized in that: The dynamic vulcanization is defined as an endpoint where at least two of the following three endpoint criteria are met: ① the kneader current curve tends to be stable with fluctuations less than 5% of the rated current; ② the rebound rate after pressing for 10 seconds by an online sample rebound hammer test is greater than 80%; ③ the gel content determined by the equilibrium swelling method is 60%-70%.
10. The method for preparing the high peel strength butyl hot melt sealant according to claim 9, characterized in that: Dynamic vulcanization is defined as the vulcanization endpoint when all three endpoint criteria are met.
Citation Information
Patent Citations
Dynamic crosslinking type hot-melt butyl self-adhesive sealant and preparation method thereof
CN111218240A